2015
DOI: 10.1371/journal.pone.0138383
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Cerebrovascular Disease Associated microRNAs Are Dysregulated in Placental Tissues Affected with Gestational Hypertension, Preeclampsia and Intrauterine Growth Restriction

Abstract: AimsTo demonstrate that pregnancy-related complications are associated with alterations in cardiovascular and cerebrovascular microRNA expression. Gene expression of 32 microRNAs (miR-1-3p, miR-16-5p, miR-17-5p, miR-20a-5p, miR-20b-5p, miR-21-5p, miR-23a-3p, miR-24-3p, miR-26a-5p, miR-29a-3p, miR-33a-5p, miR-92a-3p, miR-100-5p, miR-103a-3p, miR-122-5p, miR-125b-5p, miR-126-3p, miR-130b-3p, miR-133a-3p, miR-143-3p, miR-145-5p, miR-146a-5p, miR-155-5p, miR-181a-5p, miR-195-5p, miR-199a-5p, miR-208a-3p, miR-210-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 139 publications
3
91
2
1
Order By: Relevance
“…miRs-4709-3p, -4717-3p, 4746-3p, -1253, -103a-2-5p) or there were race-specific expression differences (miRs -30c-5p, -20a-5p, -585-5p, -4763-5p). Additionally, we wanted to include miRNAs with known associations to diseases in the vasculature systems (miR-20a-5p, miR-30c-5p, and miR-103a-2-5p)20212223. We also sought to investigate novel miRNAs that have no known targets, as their functionality may be important to hypertension etiology and/or health disparities and have only recently been cataloged by next-generation sequencing (miR-4763-5p, miR-4709-3p, and miR-4717-3p)24.…”
Section: Resultsmentioning
confidence: 99%
“…miRs-4709-3p, -4717-3p, 4746-3p, -1253, -103a-2-5p) or there were race-specific expression differences (miRs -30c-5p, -20a-5p, -585-5p, -4763-5p). Additionally, we wanted to include miRNAs with known associations to diseases in the vasculature systems (miR-20a-5p, miR-30c-5p, and miR-103a-2-5p)20212223. We also sought to investigate novel miRNAs that have no known targets, as their functionality may be important to hypertension etiology and/or health disparities and have only recently been cataloged by next-generation sequencing (miR-4763-5p, miR-4709-3p, and miR-4717-3p)24.…”
Section: Resultsmentioning
confidence: 99%
“…Our finding of expression in HUVECs suggests a role in vascular function which is supported by studies demonstrating miR-126 to be essential for angiogenesis and vascular remodelling under shear stress [29,30] as well effects on vascular endothelial growth factor A (VEGFA) [31] abundance and the production of reactive oxygen species in HUVECs [32]. miR-126 is also expressed in the placenta [33], and found to be decreased in pregnancies complicated by pre-eclampsia and fetal growth retardation [34,35]. …”
Section: Discussionmentioning
confidence: 99%
“…In humans, circulating levels of miR-21 during gestation in the mother positively correlate with evidence of fetal hypoxia [85] and evidence from in vitro studies show the participation of miR-21 in the FGR placental vascular dysfunction [86,87]. By contrast, placental miR-126 levels negatively correlate with the FGR severity [88]. Studies in umbilical endothelium from swine fetuses have shown that the expression of miRNA that targets eNOS and VEGF pathways can be modulated by maternal supplementation with an L-arginine precursor [89].…”
Section: Epigenetics and Endothelial Dysfunctionmentioning
confidence: 99%